The legend of Zelda. Twilight princess. 4 - Himekawa, Akira (VIZ Media, LLC, 2018)
"Link and Midna head for Death Mountain to dispel the darkness that is plaguing the Gorons and hopefully obtain another shard of the Shadi Crystal. If they can recover the shard they'll only need to find more piece of the Crystal. But their journey is far from over -- shadows are gathering at Hyrule Castle and there are still many grave dangers and terrible foes to face!" -- Back cover.